Предмет: Математика,
автор: rosityuk2011
Решите примеры:
3+(а-5)
х-(2+х)
7-(2-с)
-5-(у-4)
-(а-с)+(3-с)
-2-(х-а-2)
(5+х)-(х-5)
Ответы
Автор ответа:
0
3+(а-5) = 3+а-5 = -2+а
х-(2+х) = х-2-х = -2
7-(2-с) = 7-2+с = 5+с
-5-(у-4) = -5-у+4 = -1-у
-(а-с)+(3-с) = -а+с+3-с = -а+3
-2-(х-а-2) = -2-х+а+2 = -х+а
(5+х)-(х-5) = 5+х-х+5 = 10
х-(2+х) = х-2-х = -2
7-(2-с) = 7-2+с = 5+с
-5-(у-4) = -5-у+4 = -1-у
-(а-с)+(3-с) = -а+с+3-с = -а+3
-2-(х-а-2) = -2-х+а+2 = -х+а
(5+х)-(х-5) = 5+х-х+5 = 10
Похожие вопросы
Предмет: Алгебра,
автор: aisuluu58
Предмет: Русский язык,
автор: Аноним
Предмет: Математика,
автор: Аноним
Предмет: Литература,
автор: JuliyaTitova
Предмет: Алгебра,
автор: віка146